Predictors of Social Exclusion among Adolescents: The Weight of Physical Self-Concept Dimensions - Rosa González-Delgado; Antonio J. Rodríguez-Hidalgo; Rosario Ortega-Ruiz; Juan de Dios Benítez-Sillero; Javier Murillo-Moraño (MDPI AG, 2024)
Background: Social exclusion victimization among adolescents causes significant damage and harm to development and social balance. Many of the aggressions that lead to this are based on social stigmas, particularly related to physical appearance in school settings involving physical and sports activities. This study investigates the relationship between victimization through social exclusion (both manifest and subtle forms) and physical self-concept, specifically examining ability, attractiveness, physical condition, and strength. Methods: A total of 876 adolescents (mean age = 14.91; standard deviation = 1.71 years), evenly divided between boys and girls, from secondary schools in Andalusia, Spain participated. They completed a self-report questionnaire assessing physical abilities, attractiveness, physical condition, and self-perceived strength, alongside an instrument measuring experiences of social exclusion and manifest exclusion. Results: Our findings indicate that physical ability, attractiveness, and condition are negative statistical predictors of both manifest and subtle exclusion victimization, while self-perceived strength is a statistical predictor of subtle exclusion. Manifest exclusion impacts both genders similarly, but girls are more vulnerable to subtle forms of exclusion. Regardless of gender, physical ability and attractiveness significantly predict both types of exclusion. Conclusions: Our results highlight the importance of physical self-concept for wellbeing and maintaining self-concept balance. The inclusion of interventions addressing social exclusion in physical education is crucial, particularly those that work to mitigate social stigmas against adolescents who struggle in physical or sporting activities. A gender-sensitive approach should also be incorporated. The growing field of research on adolescent social exclusion, both manifest and subtle, underscores the need for further exploration of its links to physical condition, physical activity, self-perception, and societal stereotypes.